UNDERSTANDING THE CONCEPT AND BARRIERS OF TOURISM IN THE IMPLEMENTATION OF HALAL TOURISM IN CENTRAL ACEH - Rizha, Fachrur; Noviardi, Ikhwan; Harnedi, Joni (Jurnal As-Salam, 2023)
This study aims to understand tourism actors in Central Aceh concerning halal tourism and dig up information about the development of tourism in Central Aceh and the obstacles to understanding halal tourism. The research method used is a qualitative method with a qualitative descriptive approach. The subjects of this research are tourism object managers, accommodation managers (hotels/inns), transportation managers, cultural observers, culinary providers, and tourism policymakers, namely the Tourism Office of Central Aceh Regency. The study results show that tourism development in Central Aceh Regency continues to increase yearly, marked by the increasing interest of domestic and foreign tourists who visit Central Aceh Regency. Tourism development in Central Aceh is also marked by the growing economic business carried out by tourism actors. The understanding of tourism actors in Central Aceh on halal tourism is not yet comprehensive. Some tourism actors do not understand the 2014 Minister of Tourism and Creative Economy Regulation and the 2016 MUI Fatwa concerning the implementation of Halal Tourism. However, tourism actors in Central Aceh have so far implemented Sharia-based tourism services. It follows regional policies in Aceh Province regarding the application of Islamic Sharia. Barriers to understanding tourism actors in Central Aceh to halal tourism include the absence of Qanun on halal tourism in Central Aceh. There is no halal certification body in Central Aceh Regency yet. Lack of Gayo cultural literacy in society. Lack of public awareness of the cleanliness and comfort of tourism-supporting facilities and facilities.